Project SALINE: Enhancing Collaborative Learning Between Institutions Through the Power of Human Connection - Nather, Aaron (My University, 2023)
Connected learning ecologies can amplify learning outcomes for museums, visitors, and communities. A learning ecology is a physical, social, and cultural context where learning occurs. Ecological approaches to learning emphasize the need to make connections across formal, informal, and everyday education (Bevan 2016). Building relationships and strengthening human connection is crucial for maximizing learning outcomes, especially in a post-pandemic world. Museums can meaningfully contribute to broader learning ecologies alongside schools, libraries, community centers, and other information sources. However, due to many constraints, individual museums often operate in isolation and do not create connected learning experiences with other institutions. Project SALINE proposes a comprehensive, modular, and expandable connected learning solution to address the challenge. The platform provides the necessary tools to foster human connection and collaborative learning including an audio-visual hardware and software communication system, an online Learning Management System (LMS), and a customized interactive online curriculum. SALINE enhances collaborative learning for seamless and rewarding hybrid education experiences. The platform can grow and serve various learning communities, promoting an enduring and meaningful learning journey for everyone involved.
Thesis (Master's)--University of Washington, 2023